The effects of nutrition education with Pecha Kucha method on prevention of malnutrition in cancer patients undergoing radiotherapy: a randomised controlled study - Turan, Gulcan Bahcecioglu; Karaaslan, Fatma; Ozer, Zulfunaz (Bmc, 2025)
AimThe present study aimed to evaluate the effects of nutrition education by using the Pecha Kucha (20*20) presentation method on preventing malnutrition in cancer patients undergoing radiotherapy. MethodThis randomized controlled experimental study. A total of 113 patients were assessed for eligibility. Thirty-three patients declined to participate, and 20 did not meet the inclusion criteria. The final sample consisted of 60 volunteering cancer patients who met the inclusion criteria and agreed to participate. These patients were randomly assigned to either the experimental group (n = 30) or the control group (n = 30). All participants completed the study.The experimental group received nutrition education by using the Pecha Kucha method, while the control group received traditional education. Data were collected by using Personal Information Form, NRS-2002 (Nutritional Risk Screening) Assessment Form and Subjective Global Assessment (SGA). ResultsThe first and third month NRS-2002 scores of the experimental group were significantly lower than the control group(better nutritional status) (p < 0.001). After three months, the number of well-nourished individuals decreased in both groups; however, this decline was more pronounced in the control group (p = 0.001). In contrast, the intervention group largely maintained their nutritional status. NRS-2002 (beta = -0.683, p < 0.001) and SGA (beta = -3.324, p < 0.001) values were lower in the group that received pecha kucha application. ConclusionThe negative beta coefficient for NRS-2002 suggests that the Pecha Kucha training significantly reduced patients' nutritional risk. Similarly, the reduction in SGA scores reflects improved nutritional status, indicating a meaningful clinical improvement. Nutrition education provided by Pecha Kucha method is effective in preventing malnutrition in cancer patients undergoing radiotherapy. This educational method is considered to be an effective approach with high applicability in clinical settings. It is recommended that innovative and audiovisual presentation techniques such as Pecha Kucha should be utilized to strengthen responsibilities of nurses in patient education and to increase the effectiveness of education processes. Trial registrationThe study has been registered on ClinicalTrials.gov Protocol Registration (https://register.clinicaltrials.gov/prs/app/action/ViewOrUnrelease?uid=U0004RLH&ts=1&sid=S000D85L&cx=bmoiql) on 5 January 2023 (Trial Registration Number: NCT05852756).
Keywords: Nursing; Cancer; Malnutrition; Pecha Kucha; Radiotherapy